(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article contained in this translation presents the research carried out on the recordings of Racine’s Phèdre, made by Sarah Bernhard, as a case study for the analysis of sound archives in theater. It also proposes a protocol for listening to this type of document. The article represents the first objective contribution to the organization of theatrical sound studies, a field that is still little explored and in great need of guidelines.